Serbian-Slovak relations in the context of the life of the Slovak minority in the newly formed Yugoslav state after 1918 - Kmeť, Miroslav (Napredak, 2026)
The study deals with the development of Serbian-Slovak relations after 1918 in the context of the life of the Slovak minority in the newly established Kingdom of Serbs, Croats and Slovenes. The starting point of the study is the historical situation after the end of World War I, which brought about fundamental political and social changes in Central and Southeastern Europe and created new conditions for the development of international relations and for the position of national minorities. The focus is on the Slovak community living mainly in the territory of Vojvodina, which after 1918 found itself in a new state and political environment. The study offers an analysis of its social, cultural and institutional life, as well as forms of preserving national identity through education, community life, cultural activities and religious institutions. At the same time, it points to the role of the Slovak minority as a mediator of contacts between the Yugoslav environment and the Czechoslovak state, especially in relation to Czechoslovakia. The aim of the study was to point out the importance of the Slovak minority in the formation and development of Serbian-Slovak relations in the interwar period. Based on the analysis of contemporary sources and professional literature, the author points out that the Slovak community played an important role not only in preserving its own cultural identity, but also as a bridge between the two political and cultural spaces. The results of the research contribute to a deeper understanding of the position of the Slovak minority in the Yugoslav state and at the same time expand knowledge about the broader context of Serbian-Slovak relations in the first half of the 20th century.
Keywords: Slovak minority; Vojvodina; Serbian-Slovak relations; interwar period; national minorities; Kingdom of Serbs, Croats and Slovenes; Yugoslavia